Climate signals in stable carbon and hydrogen isotopes of lignin methoxy groups from southern German beech trees - Wieland, Anna; Greule, Markus; Roemer, Philipp; Esper, Jan; Keppler, Frank (Climate of the past, 2022)
Abstract. Stable hydrogen and carbon isotope ratios of wood lignin methoxy groups (δ13CLM and δ2HLM values) have been shown to be reliable proxies of past temperature variations. Previous studies showed that δ2HLM values even work in temperate environments where classical tree-ring width and maximum latewood density measurements are less successful for climate reconstructions. Here, we analyse the annually resolved δ13CLM values from 1916–2015 of four beech trees (Fagus sylvatica) from a temperate site near Hohenpeißenberg in southern Germany and compare these data with regional- to continental-scale climate observations. Initial δ13CLM values were corrected for the Suess effect (a decrease of δ13C in atmospheric CO2) and physiological tree responses to increasing atmospheric CO2 concentrations considering a range of published discrimination factors. The calibration of δ13CLM chronologies against instrumental data reveals the highest correlations with regional summer (r=0.68) and mean annual temperatures (r=0.66), as well as previous-year September to current-year August temperatures (r=0.61), all calculated from 1916–2015 and reaching p<0.001. Additional calibration trials using detrended δ13CLM values and climate data (to constrain effects of autocorrelation on significance levels) returned rsummer=0.46 (p<0.001), rannual=0.25 (p<0.05) and (p>0.05). The new δ13CLM chronologies were finally compared with the previously produced δ2HLM values of the same trees in order to evaluate the additional gain of assessing past climate variability using a dual-isotope approach. Compared to δ13CLM, δ2HLM values correlate substantially more strongly with large-scale temperatures averaged over western Europe (), whereas only weak and mainly insignificant correlations are obtained between precipitation and both isotope chronologies (δ13CLM and δ2HLM values). Our results indicate the great potential of using δ13CLM values from temperate environments as a proxy for local temperatures and, in combination with δ2HLM values, to assess regional- to sub-continental scale temperature patterns.